2008
DOI: 10.1111/j.1600-0404.2007.00932.x
|View full text |Cite
|
Sign up to set email alerts
|

ACE I/D polymorphism in Korean patients with ischemic stroke and silent brain infarction

Abstract: This study is the first report of a significant association between ACE polymorphism and ischemic stroke in the Asian population. Although no consistent associations have been found between ACE polymorphism and stroke in the populations studied to date, the ACE polymorphism may be a genetic determinant of ischemic stroke, at least in Korean patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…At the genetic level, only a few genes have been reported as risk factors for SBI to date, which include apolipoprotein (a), methylenetetrahydrofolate reductase (MTHFR) angiotensinogen (AGT) and angiotensin II type 1 receptor (AT1R) (23,24,29). We have recently studied the role of angiotensin-converting enzyme (ACE) polymorphism in the development of stroke and SBI, and found that it is associated with stroke but not with SBI (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the genetic level, only a few genes have been reported as risk factors for SBI to date, which include apolipoprotein (a), methylenetetrahydrofolate reductase (MTHFR) angiotensinogen (AGT) and angiotensin II type 1 receptor (AT1R) (23,24,29). We have recently studied the role of angiotensin-converting enzyme (ACE) polymorphism in the development of stroke and SBI, and found that it is associated with stroke but not with SBI (25).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the significance of SBI, which is known to increase the risk of developing into serious vascular diseases, such as stroke and dementia, there has been no epidemiological study on the eNOS polymorphisms in the SBI patients to our knowledge, although very few polymorphic studies of other genes have been reported (8,(23)(24)(25). Therefore, in the present study, we investigated the role of polymorphisms in the eNOS gene (-786T>C, 4a4b and 894G>T) as a risk factor for SBI.…”
Section: Introductionmentioning
confidence: 95%
“…Genetic polymorphisms of MTHFR, eNOS, ACE, and ApoE were selected based on previous findings that have indicated that the polymorphisms have biological and clinical relevance. [10][11][12][13][14] For the MTHFR 677C.T, eNOS 1894G.T, and 2784T.C polymorphisms, genotyping was performed based on the method described by Loo et al 15 The MTHFR 1298A.C, eNOS intron 4a/b, ACE I/D, and ApoE polymorphisms were genotyped using methods described by Shi et al, 16 Xin et al, 17 Ramachandran, et al 18 and Pantelidis et al, 19 respectively, with slight modifications.…”
Section: Sampling Of Subjectsmentioning
confidence: 99%
“…But recent studies show that the risk factor profile is not different in stroke subtypes questioning the validity of lacunar hypothesis [6][7][8]. Further data suggest that genetic predisposition might influence the type of stroke in patients with similar vascular risk factors [9].…”
Section: Introductionmentioning
confidence: 98%